Peningkatan Kemampuan Membaca Pemahaman Siswa Menggunakan Metode SQ3R (Survey, Question, Read, Recite, Riview) - Khaerini Haru; Sunardin Sunardin (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research is a classroom action research conducted at SDN 02 Pinceppute which aims to improve students' reading comprehension skills in Indonesian lessons with reading text material using the SQ3R method (survey, guestion, read, recite, and review) in class V SDN 02 Pinceppute. The research subjects were fifth grade students of SDN 02 Pinceppute with a total of 18 students in the odd semester of the 2019/2020 Academic Year. Data collection techniques with test techniques, non-test techniques, and field notes are carried out through direct observation in the learning process using student activity observation sheets, teacher activity observation sheets and documentation. From the data collected, it was categorized into a very poor category to a very good category and the Maximum Completeness Criteria (KKM) used at SDN 02 Pinceppute. The results showed that there was an increase in the reading comprehension skills of fifth graders at SDN Pinceputte through the application of the SQ3R method. This is evidenced by an increase in the average student learning outcomes in the first cycle of 64.4 and the second cycle of 73.1. In the first cycle, it was found that of the 18 students who took the first cycle test, there were 7 students who achieved the KKM score and 11 students had not achieved the KKM score. While in the second cycle there was an increase which showed as many as 14 students had reached the KKM score and 4 students had not reached the specified KKM, which was 70..